4D Printing of Plasmon‐Encoded Tunable Polydimethylsiloxane Lenses for On‐Field Microscopy of Microbes. Issue 3 (4th December 2021) - Mariani, Stefano; Corsi, Martina; Paghi, Alessandro; La Mattina, Antonino A.; Strambini, Lucanos; Frontini, Francesco P.; Giuseppe, Graziano Di; Barillaro, Giuseppe
Abstract: Here the 4D printing of a magnifying polydimethylsiloxane (PDMS) lens encoded with a tunable plasmonic rejection filter is reported. The lens is formed by moldless printing of PDMS pre‐polymer on a nanostructured porous silicon (PSi) templating layer. A nanometer‐thick plasmonic filter is integrated on the lens surface by in situ synthesis of Ag and Au nanoparticles (NPs) with programmed density. The filter can be designed to reject light at the plasmonic resonance wavelength of the NPs with an optical density tunable from 0 to 3 and retreive light at longer wavelengths with a pass‐to‐stop band ratio tunable from 0 to 60 dB. Swelling of PDMS in hexane and ether is used to change the NP density on the lens surface and modulate, in turn, the transmittance properties of the NP‐decorated lens over 3 orders of magnitude. The plasmon‐encoded lens is coupled to a commercial smartphone demonstrating: shaping of the emission spectrum of a white light‐emitting diode to tune the color from yellow to purple; real‐time bright‐field and fluorescence microscopy of living microbes in water, namely, the auto‐fluorescent green alga Chlorogonium sp. and the ciliated protozoan Euplotes daidaleos . Abstract : The 4D printing of a plasmon‐encoded polydimethylsiloxane (PDMS) lens is reported. The lens is moldless‐printed on nanostructured porous silicon, then in‐situ decorated with plasmonic Ag and Au nanoparticles (NPs). PDMS swelling in hexane/ether modulates the NP density tuning the lens transmittance at the resonance wavelength of a factor 1000. Coupling the plasmon‐encoded lens to a smartphone enables in‐field fluorescence microscopy of microbes.